Cooperation of C/EBP family proteins and chromatin remodeling proteins is essential for termination of liver regeneration - Jin, Jingling (Hepatology, 2014)
Liver cancer is the fifth most common cancer. A highly invasive surgical resection of the liver tumor is the main approach utilized to eliminate the tumor. Mechanisms that terminate liver regeneration when the liver reaches the original size are not known. The aims of this work were to generate the animal model which fails to stop liver regeneration after surgical resections and elucidate mechanisms which are involved in termination of liver regeneration. Because epigenetic control of liver functions has been previously implicated in the regulation of liver proliferation, we have generated C/EBPα-S193A knockin mice, which have alterations in formation of complexes of C/EBP family proteins with chromatin remodeling proteins. The C/EBPα-S193A mice have altered liver morphology and altered liver functions leading to changes of glucose metabolism and blood parameters. Examination of proliferative capacity of C/EBPα-S193A livers showed that livers of S193A mice have a higher rate of proliferation after birth, but stop proliferation at the age of 2 months. These animals have increased liver proliferation in response to liver surgery as well as CCl(4)-mediated injury. Importantly, livers of C/EBPα-S193A mice fail to stop liver regeneration after surgery when livers reach the original, pre-resection, size. The failure of S193A livers to stop regeneration correlates with the epigenetic repression of key regulators of liver proliferation C/EBPα, p53, FXR, SIRT1, PGC1± and TERT by C/EBPβ-HDAC1 complexes. The C/EBPβ-HDAC1 complexes also repress promoters of enzymes of glucose synthesis PEPCK and G6Pase. CONCLUSIONS: Our data demonstrate that a proper co-operation of C/EBP and chromatin remodeling proteins is essential for the termination of liver regeneration after surgery and for maintenance of liver functions.